MANUFACTURERS AND SECURITY PROVIDERS: A CONCEPTUAL ESSAY - Petre, Silviu; Ciuperca, Ella (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
This article aims to contribute to the theoretical clarification of certain widely used terms in scholarly literature as well as in public statements made by policymakers, pundits, media people but insufficiently exaplained, namely security producers and security consumers. Although frequently present, neither political science nor international relations literature have grappled with them, therefore rendering scholars incapable to grasp the complexity of inter-state position.